Stochastic and Differential Activation of σB and PrfA in Listeria monocytogenes at the Single Cell Level under Different Environmental Stress Conditions - Guldimann, Claudia; Guariglia-Oropeza, Veronica; Harrand, Sophia; Kent, David; Boor, Kathryn J.; Wiedmann, Martin (Frontiers in Microbiology, 2017)
During host infection, the foodborne pathogen Listeria monocytogenes must sense and respond to rapidly changing environmental conditions. Two transcriptional regulators, the alternative sigma factor B (σB) and the Positive Regulatory Factor A (PrfA), are key contributors to the transcriptomic responses that enable bacterial survival in the host gastrointestinal tract and invasion of host duodenal cells. Increases in temperature and osmolarity induce activity of these proteins; such conditions may be encountered in food matrices as well as within the host gastrointestinal tract. Differences in PrfA and σB activity between individual cells might affect the fate of a cell during host invasion, therefore, we hypothesized that PrfA and σB activities differ among individual cells under heat and salt stress. We used fluorescent reporter fusions to determine the relative proportions of cells with active σB or PrfA following exposure to 45°C heat or 4% NaCl. Activities of both PrfA and σB were induced stochastically, with fluorescence levels ranging from below detection to high among individual cells. The proportion of cells with active PrfA was significantly higher than the proportion with active σB under all tested conditions; under some conditions, nearly all cells had active PrfA. Our findings further support the growing body of evidence illustrating the stochastic nature of bacterial gene expression under conditions that are relevant for host invasion via food-borne, oral infection.